Gambling in an Australian First Nations Community in the COVID-19 Era: The Importance of Supporting Community Responses and Responsibilizing Industry and Governments for Gambling Harms - MacLean, Sarah; Kanjere, Anastasia; Griffin, Tiffany; Portelli, Jai; Caluzzi, Gabriel; Savic, Michael; Pennay, Amy (Critical Gambling Studies)

(untitled) (University of Alberta Library, 2024)
We report on a collaborative qualitative study to identify gambling expenditure trajectories associated with COVID-19 restrictions on in-venue gambling for people in a regional First Nations Community in Victoria, Australia. Drawing from interviews with 20 First Nations people and seven workers, we use three people’s stories to illustrate experiences associated with: reduced gambling expenditure; little change in gambling expenditure; and increased gambling expenditure. Across each trajectory, many participants took up or increased online gambling during restrictions. The largest proportion returned to pre-COVID-19 gambling expenditure once restrictions eased. Some took the opportunity of a forced break from in-venue gambling to reassess its role in their lives, and a further small proportion spent more money on gambling after the pandemic than prior to it. We highlight the importance of Community in participants’ capacities to manage gambling during this period. Participants described the presence of Community members at in-venue gambling as limiting their spending, something that became unavailable when gambling online at home during lockdowns. Willpower was identified as most participants’ preferred means of managing gambling. This worked for some, but others noted that the ubiquity of online gambling products and ongoing effects of trauma and disadvantage stymied their efforts. As some participants insisted, the gambling industry and governments that are its beneficiaries perpetuate colonization by extracting money from First Nations peoples, with gambling harm attributed to Indigeneity rather than poverty resulting from colonization and dispossession. Thus, First Nations Communities and individuals are held responsible for problems that are largely not of their making.